1996
DOI: 10.2307/3236421
|View full text |Cite
|
Sign up to set email alerts
|

Impact of different sheep grazing intensities on salt marsh vegetation in northern Germany

Abstract: Abstract. Mainland salt marshes in Schleswig‐Holstein (northern Germany) have been grazed intensively by sheep for several decades. In 1988 experimental sites were established in the lower and middle salt marsh of Sönke‐Nissen‐Koog and subjected to different grazing intensities. From 1989 to 1993 the impact of sheep grazing on the composition and structure of the salt marsh vegetation was studied through the yearly analysis of permanent plots, vegetation mapping and measurements of the vegetation height. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
88
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(97 citation statements)
references
References 18 publications
6
88
2
1
Order By: Relevance
“…This has been confirmed by surveys of changes in the botanical composition of pastures following a reduction of management intensity or stocking rates (e.g. Kiehl et al, 1996;Hart and Ashby, 1998;Marriott et al, 2004). However, a very low stocking rate is also assumed to reduce plant diversity as a result of competitive exclusion, where the high productivity of some species dominates plant species that cannot compete for light (Grime, 1979).…”
Section: Introductionmentioning
confidence: 73%
“…This has been confirmed by surveys of changes in the botanical composition of pastures following a reduction of management intensity or stocking rates (e.g. Kiehl et al, 1996;Hart and Ashby, 1998;Marriott et al, 2004). However, a very low stocking rate is also assumed to reduce plant diversity as a result of competitive exclusion, where the high productivity of some species dominates plant species that cannot compete for light (Grime, 1979).…”
Section: Introductionmentioning
confidence: 73%
“…Some research has demonstrated, however, that management type can be even more important than salinity in influencing vegetation patterns (Amiaud et al 1998;Jutila 2001;Piernik 2012). Moreover, the vegetation pattern can be affected in a different way by different intensities of cutting and grazing (Bakker 1989;Kiehl et al 1996). We investigated relatively small areas directly affected by salt/ brackish water and, there, it was difficult to determine if the area is permanently mown or grazed (sometimes both).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however the number of livestock is increasingly oversized (Yang, 1999). Excessive grazing can affect not only the community structure of vegetation, influencing microhabitat selection and thermoregulatory behavior during terrestrial migration of frogs (Kiehl et al, 1996;Eccard et al, 2000;Hayes and Holl, 2003) but also threaten small waterbodies used for reproduction and overwintering by R. kukunoris through the actions of trampling and erosion (YQ, pers. obs.).…”
Section: Discussionmentioning
confidence: 99%